Multispectral Imaging with Raspberry Pi for Assessment of Plant Health Status - Bosse, Jan Lukas; Adhiwibawa, Marcelinus A. S.; Brotosudarmo, Tatas H.P. (Ma Chung Research Center for Photosynthetic Pigments, 2019)
Non-destructive measurement of plant chlorophyll concentration using the normalized difference vegetation index (NDVI) has long been standard practice to determine the plant health status. This is, because the NDVI value is correlated with the chlorophyll concentration which in turn is highly correlated with other vital plant parameters such as nitrogen and magnesium concentration. Initially the NDVI values were obtained from satellite imagery and thus could only be used to assess the health status of bigger ecosystems like forests and crop fields. With the introduction of handheld chlorophyll meters like the Chlorophyll Meter SPAD-502 Plus made by Konica Minolta, the same principle could be used to determine the chlorophyll concentration of single leaves. However, these devices still have one major shortcoming: They can only measure the chlorophyll concentration on one single spot on the leaf at a time. But depending on the species the chlorophyll concentration tends to vary significantly over the leaf. To overcome this shortcoming, we developed our PlantAnalyzer which offers better spatial resolution of the NDVI values and hence the chlorophyll concentration. Its technical realization and precision shall be elaborated in the following article.